Naming practices with special reference to Xitsonga personal names : an onomastic analysis - Baloyi, Famandha Reckson (My University, 2014)
Refer to the document
Thesis ((M.A. (African Languages)) -- University of Limpopo, 2015
Keywords: Naming; Personal names; Onomastic analysis; Xitsonga names; Onomastics; Names, Personal